EFEKTIFITAS KOMPETISI PERADILAN ANTARA PENGADILAN NIAGA DAN PENGADILAN NEGERI TERHADAP GUGATAN ACTIO DALAM SENGKETA KEPAILITAN PAULINA - , Suhardi La Maira ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Actio Pauliana is an authority given to a Curator to cancel a bankrupt debtorâs lawful act which is non-obligatory and done before the bankruptcy verdict is stated by the court so that it harms a creditor interest. Curator, for the sake of bankrupt property, can ask a court, whether District Court or Commercial Court, to cancel all debtorâs lawful acts. The regulation about Actio Pauliana is written on The Book of Civil Law chapter 1341 junction Chapter 41 to Chapter 47 Act No.37 Year 2004 About Bankruptcy and Postponement of Debt Payment Obligation. The research is aimed at finding out the effectiveness of commercial court and district court in actio pauliana in bankruptcy dispute. The research is a normative jurisdiction research which consists of library research and field research. Primary data are acquired from the respondents on the field, namely the judges of Central Jakarta Commercial Court, judges of District Court and Bankruptcy Curator with interview and questionnaire methods, meanwhile secondary data are acquired from library research. Effectiveness of courts competency, both commercial court and district court, can be measured with several indicators, namely (1) the term of cases solving, (2) the size of cases cost, (3) the nature and way of proving, (4) the lawful effects caused by both verdicts, and (5) lawful effort that can be done to the verdict which was resulted from the authority to judge. The research results show that the competence of Commercial Court is proven to be more effective to judge actio pauliana suit in bankruptcy cases than the competence of District Court, in protecting the creditor from harmful nonobligatory lawful acts of a debtor and faster in giving lawful certainty for the creditor, the debtor, and the involved third party. The verdict of Commercial Court has a lawful implication, namely it can be executed directly to pay the debts of the creditors, because the examination process of actio pauliana in Commercial Court is a serie in terms of bankruptcy in which public seizure is applied.